2023
DOI: 10.3389/fnut.2023.1118752
|View full text |Cite
|
Sign up to set email alerts
|

The influence of curcumin additives on the viability of probiotic bacteria, antibacterial activity against pathogenic microorganisms, and quality indicators of low-fat yogurt

Abstract: Curcumin is a nutraceutical with unique anti-inflammatory, anti-oxidative, and antimicrobial properties. In this study, we aimed to examine the advantages of the use of water dispersible and highly bioavailable form of standardized turmeric extract (Curcuma longa L.)—NOMICU® L-100 (N) in the formulation of probiotic yogurt in comparison with the standard turmeric extract (TE). The antimicrobial activity of both supplements was studied and compared in the context of gram-positive and gram-negative bacteria, yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…The combined effects of curcumin and organic acids enhance overall health in layer chickens. Buniowska-Olejnik et al (2023) reported that curcumin promotes the growth of various lactic acid bacteria and inhibits the colonization of harmful bacteria in the intestines, as demonstrated by Nascimento et al (2019).…”
Section: Hen-day Egg Laying Performance Feed Conversion Ratio and Wat...mentioning
confidence: 83%
“…The combined effects of curcumin and organic acids enhance overall health in layer chickens. Buniowska-Olejnik et al (2023) reported that curcumin promotes the growth of various lactic acid bacteria and inhibits the colonization of harmful bacteria in the intestines, as demonstrated by Nascimento et al (2019).…”
Section: Hen-day Egg Laying Performance Feed Conversion Ratio and Wat...mentioning
confidence: 83%